2019
DOI: 10.1016/j.dib.2019.104647
|View full text |Cite
|
Sign up to set email alerts
|

How far has Africa gone in achieving sustainable development goals? Exploring African dataset

Abstract: The dataset describes the status of African countries on the attainment of Sustainable Development Goals (SDGs). Datasets on SDG Index (SDGI) scores and other selected variables were compiled from relevant secondary sources. Graphical illustrations were used to describe the type of association existing between the SDGI scores and each of the selected variables to corroborate [1]. Further rigorous statistical analysis can be carried out using these data, in conjunction with other datasets to establish scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…African countries with high percentage of total population in extreme poverty, high Corruption Perceptions Index (CPI) ranks and high number of conflict events have higher GHI scores. It was also reported that there is a positive association between the prevalence of stunting and the attainment of SDGs in Africa by 2030 (Smith and Haddad, 2015;Otekunrin et al 2019a;Otekunrin et al, 2019c).…”
Section: Hunger In Africamentioning
confidence: 93%
See 1 more Smart Citation
“…African countries with high percentage of total population in extreme poverty, high Corruption Perceptions Index (CPI) ranks and high number of conflict events have higher GHI scores. It was also reported that there is a positive association between the prevalence of stunting and the attainment of SDGs in Africa by 2030 (Smith and Haddad, 2015;Otekunrin et al 2019a;Otekunrin et al, 2019c).…”
Section: Hunger In Africamentioning
confidence: 93%
“…For example, the Central African Republic (CAR), Madagascar and Nigeria had higher stunting prevalences of 47.4%, 46.1% and 37%, respectively, in 2019 compared to those in 2010. It was also reported that there is a positive association between the prevalence of stunting and the attainment of SDGs target in Africa by 2030 (Otekunrin et al, 2019c).…”
Section: Patterns Of Ghi Scores In Africa Before Covid-19 Pandemicmentioning
confidence: 94%
“…In 2019, 135 million people in 55 countries of the world suffered from acute food crises, with 73 million of them coming from 36 countries in Africa (FAO et al 2019;FSIN GRFC 2020). Otekunrin et al 2019c).…”
Section: Prevalence and Severity Of Hunger In Africa In Three Decadesmentioning
confidence: 99%
“…Sustainable Development Goal 2, developed in 2016, aims at attaining zero hunger in the whole world by the year 2030, but hunger, together with malnutrition, remains a hindrance to growth and development in most regions, specifically in Africa (FAO et al 2017). The question remains whether food security will be attained, as many African countries are dealing with problems of hunger, coupled with COVID-19, conflicts, climate change, poverty, and ignorance (Otekunrin, Momoh, Ayinde and Otekunrin 2019;Shiuan-Huei et al 2014).…”
Section: Introductionmentioning
confidence: 99%